2012
DOI: 10.1073/pnas.1113966109
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the HLA-DO/HLA-DM complex by FRET and mutagenesis

Abstract: HLA-DO (DO) is a nonclassic class II heterodimer that inhibits the action of the class II peptide exchange catalyst, HLA-DM (DM), and influences DM localization within late endosomes and exosomes. In addition, DM acts as a chaperone for DO and is required for its egress from the endoplasmic reticulum (ER). These reciprocal functions are based on direct DO/DM binding, but the topology of DO/DM complexes is not known, in part, because of technical limitations stemming from DO instability. We generated two varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Although the structural details of these interactions have not yet been reported, efforts using mutagenesis, FRET, and molecular modeling (40,41) suggest that a large lateral interface of DO with DM or of DM with DR is involved. This interface contrasts sharply with the interaction surface of m152, which exploits its α1α2 pd and its α3 Ig-like domains.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structural details of these interactions have not yet been reported, efforts using mutagenesis, FRET, and molecular modeling (40,41) suggest that a large lateral interface of DO with DM or of DM with DR is involved. This interface contrasts sharply with the interaction surface of m152, which exploits its α1α2 pd and its α3 Ig-like domains.…”
Section: Resultsmentioning
confidence: 99%
“…DO αβ dimers associate tightly with DM molecules, and are retained in the ER in the absence of DM, suggesting that in DO-positive cells DM and DO move in concert to endosomes (Figure 4) (95). Studies using Förster (Fluorescence) Resonance Energy Transfer (FRET) and mutational analysis that defined the DM/DR interface suggested that that DO and DR bind to the same region of DM (96). Recently the crystal structure of the DO/DM complex confirmed this, and demonstrated an apparent displacement of a segment of the DO α-chain α-helix compared with that of this α-helix in MHC-II-peptide complexes, which may reflect the conformational alteration that DM imparts to induce the dissociation of low affinity peptides (97).…”
Section: Peptide Binding To Mhc-ii Moleculesmentioning
confidence: 99%
“…To determine whether this interaction is pH-sensitive, we examined binding in real time, using biolayer interferometry (Octet). We immobilized sDM on Octet sensors via DMα C-terminal biotin (27) and incubated the sensors with mAb b12 Fab at varying pH (4.7-7.2). The Fab/DM interaction rapidly achieved equilibrium, allowing comparison of equilibrium signal magnitude at each pH (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For biotinylation, an AviTag sequence (Avidity, Aurora, CO) was added to the C-terminus of the sDMα chain (27), and biotinylation was performed according to manufacturer's instructions. Human mAb b12 and mAb b6 (both IgG1-κ, anti-HIV-1 gp120) were obtained from Dr. Dennis Burton, Scripps Research Institute, La Jolla, CA (28).…”
Section: Methodsmentioning
confidence: 99%